2013
DOI: 10.1007/s00114-013-1065-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity affects colony survivorship in commercial honey bee colonies

Abstract: Honey bee (Apis mellifera) queens mate with unusually high numbers of males (average of approximately 12 drones), although there is much variation among queens. One main consequence of such extreme polyandry is an increased diversity of worker genotypes within a colony, which has been shown empirically to confer significant adaptive advantages that result in higher colony productivity and survival. Moreover, honey bees are the primary insect pollinators used in modern commercial production agriculture, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 34 publications
2
64
0
Order By: Relevance
“…Our findings support the idea that variance-based selection-whereby intercolony variance is reduced by multiple mating-may explain the evolution of polyandry in social insects [24]. Furthermore, based on previous theoretical and empirical data concerning the threshold mating frequency on the polyandry continuum of honeybees [24,25], our data are consistent with an effective paternity frequency of approximately 7 maximizing the effects of polyandry in this system. This is significantly lower than the average observed mating frequency for A. mellifera and lower than what is typically tested when attempting to determine if intracolonial genetic diversity influences behaviour and colony fitness [15,18].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings support the idea that variance-based selection-whereby intercolony variance is reduced by multiple mating-may explain the evolution of polyandry in social insects [24]. Furthermore, based on previous theoretical and empirical data concerning the threshold mating frequency on the polyandry continuum of honeybees [24,25], our data are consistent with an effective paternity frequency of approximately 7 maximizing the effects of polyandry in this system. This is significantly lower than the average observed mating frequency for A. mellifera and lower than what is typically tested when attempting to determine if intracolonial genetic diversity influences behaviour and colony fitness [15,18].…”
Section: Discussionsupporting
confidence: 89%
“…The reduction of genetic diversity due to beekeeping practices is one of the several causes suggested (Oldroyd 2007) and has had an important impact on managed colonies (De la Rúa et al 2013). Studies have demonstrated that reduced levels of intra-colonial genetic diversity affect colony fitness (Tarpy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lack of genetic diversity within a colony due to poor queen mating success because of low queen quality or lack of healthy drones can disrupt colony homeostasis. This in turn could lead to economic losses due to beekeepers having to re-queen their colonies or ultimately colony loss [45,46]. As the mechanisms underlying the correlation between mating success and colony health are not fully understood, bee breeders can ensure the quality of reproductive castes only if these mechanisms are further elucidated.…”
Section: Mating Success Health and Quality Of Reproductive Castesmentioning
confidence: 99%
“…The queen takes 1-5 mating flights during which she mates with an average of 12-14 drones [46] storing all the sperm she will use during her lifetime. After mating, queens undergo behavioral, physiological and transcriptional changes signaling their new role in the hive.…”
Section: Mating Success Health and Quality Of Reproductive Castesmentioning
confidence: 99%